PREDISPOSING FACTORS OF ATRIAL FIBRILLATION IN PATIENTS AFTER ANATOMIC LUNG RESECTION - V. A. Zhikharev; V. A. Porkhanov; A. S. Bushuev; I. Yu. Sholin; V. A. Koryachkin (Вестник анестезиологии и реаниматологии)
Atrial fibrillation (AF) remains to be one of the most common complications that occur after thoracic surgery; its frequency makes from 4 to 37%. This type of complication can significantly extend the recovery period for the patients after anatomic lung resection and increase the short-term and long-term mortality.Subjects and methods. Data of 183 patients who underwent extensive anatomic lung resections due to malignant neoplasms were retrospectively analyzed. The following was evaluated: the impact of surgery approach (thoracotomy or VATS) and the type of anatomic lung resection, peri-operative fluid balance and severity of pain syndrome as per Visual Analogue Scale on the incidence of AF. Statistical analysis was performed using Student's t-test, non-parametric χ2 test and Mann – Whitney test, as well as a multidimensional logistic regression with standardization of indicators and odds ratio calculation.Results. In the early post-operative period, AF developed in 40 patients. It was found out that with increasing age, the rate of intra-operative infusion and positive fluid balance during the first day of the post-operative period, the risk of post-operative AF went up in thoracic patients.